Kerusakan Roller pada Conveyor Kedatangan - Ismail , KGS. M; Suwono, Niedya Inten; Al Qorni, Uwais; Rizqi Putra Iswanto, Aldiansyah; Friskiana, Ni Made Savitri; Adonia Kapisa, Yunice (Program Studi Teknik Mekanikal Bandar Udara, 2023)
Conveyors are a type of material handling equipment designed to transport materials horizontally or vertically, powered by either a drive motor or gravity. Bottom ash conveyors play a crucial role in transporting bottom ash from the discharge of submerged scraper conveyors (SSC). One common issue encountered with these conveyors is the damage to the return side roller idlers, occurring approximately five times per month. Therefore, it is necessary to conduct an analysis to identify the causes of damage to the bottom ash conveyor's roller idlers, with the aim of providing recommendations to address the problem and reduce the risk of recurring damage. After conducting the analysis and research, it was found that the main causes of roller idler damage are abrasion, corrosion, suboptimal Belt Cleaner performance, and inadequate roller specifications used in the conveyor system. Roller damage can result in the cessation of ash conveyor operations, potentially leading to environmental pollution as bottom ash cannot be transferred to the silo. Consequently, it is crucial to identify the root causes of these issues in order to enhance the reliability of the bottom ash conveyor system. The purpose of this research is to study the mechanical damage that occurs in the conveyor system, determine the appropriate maintenance practices for the conveyor system, identify the appropriate roller specifications for the conveyor system.